PENGARUH EMISI GAS RUMAH KACA SEBAGAI INDIKATOR KINERJA LINGKUNGAN DAN PENGUNGKAPAN LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Shabrina Khansa; Andrian Budi Prasetyo (Diponegoro Journal of Accounting, 2022)
This study aims to examine the relation between environmental performance and environmental disclosure with firm value. This study uses greenhouse gas emission as environmental performance indicator and Carbon Disclosure Project rating as environmental disclosure indicator. Market value of equity is used to define firm value as dependent variable. This study uses secondary data from firm’s financial report accessed through Bloomberg Terminal and Bursa Efek Indonesia webpage. Purposive sampling method is used to gather sample within the year of 2011 to 2017. This study examine 653 company and gathered 42 sample. There is no significant relation between greenhouse gasses emission and firm value observed in this study, eventhough it shows an insignificant negative relation. We also didn’t found significant relation between environmental disclosure with firm value. We examined interactive effect between environmental performance and disclosure and also didn’t found a significant relation to firm value.